2016
DOI: 10.1155/2016/8528270
|View full text |Cite
|
Sign up to set email alerts
|

High Triglycerides Are Associated with Low Thrombocyte Counts and High VEGF in Nephropathia Epidemica

Abstract: Nephropathia epidemica (NE) is a mild form of hemorrhagic fever with renal syndrome. Several reports have demonstrated a severe alteration in lipoprotein metabolism. However, little is known about changes in circulating lipids in NE. The objectives of this study were to evaluate changes in serum total cholesterol, high density cholesterol (HDCL), and triglycerides. In addition to evaluation of serum cytokine activation associations, changes in lipid profile and cytokine activation were determined for gender, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…We found also that LDCL1 and HDCL1 have positive and negative associations with PC1 cytokines, respectively. Changes in the serum level of lipids have been demonstrated in hantavirus-infected patients [2,66,67]. Our results provide more data contributing to the understanding of the role of lipids in pathogenesis of NE.…”
Section: Discussionsupporting
confidence: 60%
“…We found also that LDCL1 and HDCL1 have positive and negative associations with PC1 cytokines, respectively. Changes in the serum level of lipids have been demonstrated in hantavirus-infected patients [2,66,67]. Our results provide more data contributing to the understanding of the role of lipids in pathogenesis of NE.…”
Section: Discussionsupporting
confidence: 60%
“…In my study, we found that there was a significant and positive correlation between VEGF with TG, the high TG concentration, so the high VEGF concentration too in my study, we found that there was no significant correlation between VEGF and cholesterol total, LDL, and HDL. Like research by Martynova et al reported that high TGs were associated with high serum VEGF [14]. However, different research by Sun et al that there were no significant relationships between VEGF and any of the following factors such as sex, age, BMI, HbA1c, FBG, TG, TC, HDL-C, and LDL-C at type 2 DM [15].…”
Section: Discussionmentioning
confidence: 87%
“…A previous study revealed that VEGF-A expression alone initially leads to vessel enlargement followed by a loss of pericytes [ 19 ]. A high cholesterol diet might increase the expression of serum VEGF-A in nephropathia epidemica [ 20 ]. Our study indicated that VEGF-A and VEGFR-2 expression levels dramatically increased from week 4 to 12, and the correlation between LDL-C and VEGF-A/VEGFR-2 was positive.…”
Section: Discussionmentioning
confidence: 99%